Identifying Factors Leading To Gold Losses During The Fabrication Process And Assessing Its Impact On The Smes Jewellery Industry. - et. al., Saadiah Kaspin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study intended to determine the level of awareness by the Kelantan Jewellers House on how much is the impact of gold losses during the jewelry-making process to their business. The study focuses more on Kelantan State due to their popularity and existence of a chain of small and traditional craftsmen. Most local operators are still preserving the traditional way of fabrication and production techniques, tools, methods whilst maintaining the Malay aesthetic value in all aspects of fabrication. This unique value proposition inherited from their legacy lineage was taught throughout the generations and now adopted by the younger craftsmen in rank. Ironically, the manual process and traditional fabrication techniques were seen as less efficient due to the higher amount of gold scrap as compared to modern techniques. Hence, this paper aims to ascertain the findings and to validate the assumptions that the manual and traditional technique does indeed contributes to a higher amount of gold losses that adversely affecting the yield and economic returns of the small fabricators in Kelantan, whilst formulating the right action plans to mitigate and resolve the issues effectively.